Oxford International primary English student book For grade 3 - Myrby,Myra (Lahore Oxford university press, 2022)
A complete six-year primary English language and literacy course that teaches young learners the language and skills they need to become confident, independent students, and supports the transition to secondary school. Inspire and engage young learners with a range of culturally diverse fiction, non-fiction and poetry Integrate wellbeing and an enquiry-based approach to put every child at the heart of the learning experience Monitor children's progression with Revise and Check assessments Support the needs of all learners with a course that maps to a variety of curricula, including English National Curriculum and Oxford International Curriculum Cater to every student's needs with differentiation and extension ideas built into every unit Easily connect to Oxford Primary readers through correlation to Oxford Levels Enable development for students with English as an Additional Language with practical language support Enhance the learning experience with comprehensive digital content available via school subscription
Keywords: English - Text Book